Financial impact of the IMO 2020 regulation on dry bulk shipping - Christos Sigalas (Maritime Transport Research, 2022)
The effectiveness of the IMO's sulfur cap regulation in January 2020 disrupted the established business paradigm in some maritime shipping sectors. In the absence of a protection scheme by policymakers, the business paradigm in dry bulk shipping sector shifted, because the additional cost associated with the more expensive IMO sulfur compliant fuel had been passed to ship-owners, instead of charterers. The purpose of this paper is to demonstrate the business paradigm disruption that was caused by the IMO 2020, by examining the covariance between the freight rates and their Time Charter Equivalent (TCE) rates around the IMO 2020 effectiveness date, as well as to quantify the financial impact of the IMO 2020 regulation to ship-owners, by modeling TCE, maximizing TCE function, and running TCE sensitivity analyses under various scenarios of price spread between the high sulfur and IMO compliant fuel oils before and after the introduction of the IMO 2020. The results of this study indicate that increased price of IMO compliant fuel oils and charterers’ bargaining power, had curtailed ship-owners’ gross profit margins. Although not a silver bullet, slow steaming can alleviate shrunken profit margins. These findings provide valuable insights for policymakers in calibrating future emission-related regulations to be equitable for all stakeholders engaged in seaborne transportation.